The state, non-state community security actors, and violence in Swaziland, 2000-2011 - Simelane, Hamilton (Faculty of Humanities, University of the Free State, 2013)
Research and analysis of the Swaziland security sector have, up to now, escaped the attention of scholars. This is in spite of developments that show that different segments of the Swazi population have voiced security concerns that range from insecurity of property to economic security concerns that undermine their efforts for economic well-being and reproduction. It is also in spite of the fact that rural communities have constructed community security frameworks that go beyond state-centric approaches to security. This article shows that rural Swazi communities have established non-state community security frameworks that operate outside the realm of the state and in the process contribute to the revision of the concept of security by emphasizing economic threats instead of military ones and focusing on community and individual security rather than regime security. However, the author argues that this transition should not be romanticized, because in Swaziland the development of nonstate community security actors has been accompanied by violence and a general disregard for people’s rights. The researcher argues that this is because non-state community security actors developed in the context of a non-democratic state that has entrenched a culture of disrespect for human rights.
Keywords: Human; Security; Non-state actors; Theft; Police; Violence; State; Corruption; Human rights abuse; Swaziland